Assessment of cardiovascular sympathetic function tests in premenstrual syndrome patients visiting tertiary care hospital: A case–control study - Kulshreshtha, Megha; Gaur, Naveen; Gupta, Varuna; Kodidala, Satyanath Reddy (Asian Journal of Medical Sciences, 2021)
Background: Premenstrual syndrome (PMS) is a stress-induced disorder and is showing a rising prevalence but its etiopathogenesis is not yet understood. Stress disturbs the balance of the sympathetic and parasympathetic nervous system. Alteration in heart rate and blood pressure is the most important physiological response following stress-induced sympathetic changes. Aims and Objectives: The present study was designed to test the hypothesis of an association between sympathetic functions and PMS and to observe the degree of changes (if any) in these sympathetic functions. The study also aims to provide timely interventions to prevent the development of cardiovascular complications and improve lifestyle. Materials and Methods: A Menstrual Distress Questionnaire was used to evaluate physical, emotional, and behavioral symptoms accompanying the menstrual cycle of the subjects who fulfilled the inclusion criteria. Based on the scores obtained by their questionnaire, subjects with the higher scores formed the PMS group, while the age-matched females with low score served as controls. Cardiovascular sympathetic functions were assessed by standardized, simple, non-invasive tests which included Handgrip test and orthostatic hypotension test. Unpaired Student’s t-test was used for statistical analysis. Results: The results revealed that the sympathetic reactivity is insignificantly higher in PMS group during the follicular phase. During the luteal phase, sympathetic activity is significantly increased. Conclusion: PMS involves psychoneuroendocrinal turmoil, thus early screening of high-risk groups and interventions such as relaxation techniques and lifestyle modification can prevent further cardiovascular complications in patients of high sympathetic responses.